Prevalensi dan Faktor yang Berhubungan dengan Terjadinya Beban Gizi Ganda pada Keluarga di Indonesia - Astuti, Nur Fitri Widya; Huriyati, Emy; Susetyowati, Susetyowati (Media Kesehatan Masyarakat Indonesia, 2020)
Urbanization and economic rapid developments in the developing countries cause a nutrition transition. They affect the household dual burden of malnutrition in which there is overnutrition and undernutrition occuring at the same time in a household. This study proposed to calculate the prevalence of household dual burden malnutrition and find its determinants. This cross-sectional study use the Indonesian Family Life Survey (IFLS) 2014 data with total of 6468 families were enrolled as the sample of the study. The household dual burden malnutrition indicator is represented by mother and children’s nutritional status. Descriptive analysis and chi-square test were used in this study. The study found that the prevalence of household dual burden malnutrition in Indonesia is 8.27% in which the Borneo and Eastern Indoesia region has the higest prevalence. Maternal age (p = 0.001), maternal education (p = 0.022), number of children (p = 0.001), and number of household members (p = 0.001) were having significant correlation (p<0.05) with the household dual burden malnutrition in Indonesia. Further study by using longitudinal design is needed to find the predictors of it so the government can formulate an effective and efficient intervenion to prevent adverse effects of household dual burden malnutrition to the community.